Extraction of proteins from animal tissues by the SDS 2% protocol (Research, Society and Development, 2020)
Under extensive territorial conditions in Brazil there are many needs of resources to conduct research. Many Federal and State Universities rely on resources to invest in technologies for analysis in biological systems. Innovations that allow reducing the costs in the execution of the research, makes them practical at the field level and responsive in the realization of the research. For this purpose, a 2% sodium dodecyl sulfate (SDS) protein extraction protocol was proposed in order to reduce the amount of solvents organic scans used, without harming the viability of proteins, the feasibility of other proteomic analysis techniques: SDS-PAGE and Mass Spectrometry, precisely due to the reduction of the accumulation of waste produced by cell lysis. Considering SDS as a component in the SDS-PAGE process, this does not cause accumulation of residue by organic solvents external to the technique, besides cheapening costs and reducing the toxicological effect in the laboratory. The results obtained showed that this protocol proves to be viable for protein extraction from animal tissues, proven by the SDS-PAGE technique that allowed a clear visualization of the fragments of the extracted proteins and the absence of protein traces from excess cell lysis.